2012
DOI: 10.1371/journal.pone.0033290
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Non-Genetic Influences during Pregnancy on Infant Global and Site Specific DNA Methylation: Role for Folate Gene Variants and Vitamin B12

Abstract: Inter-individual variation in patterns of DNA methylation at birth can be explained by the influence of environmental, genetic and stochastic factors. This study investigates the genetic and non-genetic determinants of variation in DNA methylation in human infants. Given its central role in provision of methyl groups for DNA methylation, this study focuses on aspects of folate metabolism. Global (LUMA) and gene specific (IGF2, ZNT5, IGFBP3) DNA methylation were quantified in 430 infants by Pyrosequencing®. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 66 publications
(76 reference statements)
3
108
1
4
Order By: Relevance
“…The following possible confounders were based on expertise and literature review (Steegers-Theunissen et al 2009, Obermann-Borst et al 2011, McKay et al 2012.…”
Section: Covariatesmentioning
confidence: 99%
“…The following possible confounders were based on expertise and literature review (Steegers-Theunissen et al 2009, Obermann-Borst et al 2011, McKay et al 2012.…”
Section: Covariatesmentioning
confidence: 99%
“…Examples of such modifications are known from some types of cancer, where hypomethylation of oncogenes and hypermethylation of tumour suppressor genes are supposed components in cancer development [2,4,5]. Epigenetic profiles are influenced by genetics [6][7][8], but ageing and environmental factors including diet, chemicals and smoking may take centre-stage in the control of DNA methylation [9][10][11][12]. Studies have indicated that DNA methylation may play a role in metabolic diseases such as diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic differences may not only be secondary to exposure (ART or other in utero exposure) but may also be dependent on the maternal genotype. A recent study found that polymorphisms in genes involved in folate absorption and metabolism may affect DNA methylation patterns (McKay et al 2012). Abnormal methylation of paternal DNA is also important to study because DNA methylation may be altered in the sperm of men with infertility.…”
Section: Resultsmentioning
confidence: 99%